Pengaruh Temperatur Karbonisasi Bambu Betung Terhadap Wettability Dan Kekasaran Permukaan Material - Akhsan, Wildan; Bandem Adnyana, I Wayan; Wijaksana, Hendra (Teknik Desain Mekanika; Vol 10 No 2 (2021): April 2021 : Teknik Desain Mekanika, 2021)
Abstract Indonesia is a country that has a tropical climate, the temperature in a tropical climate has an average of 30oC - 35oC with an average humidity level of 70% - 80%. It takes 60% of electricity consumption every day to get the required standard of air comfort at an air temperature of 22oC - 25oC and a relative humidity level of 40% - 60% using an air conditioning system. However, the impact of the use of refrigerants on the AC cooling system can cause an unfavorable environment and can also trigger global warming to increase. In connection with this, a cooling system that is more energy efficient and friendly to the environment has begun to be developed, namely a direct evaporative cooling system that utilizes the sensible heat of the outside air to evaporate the water layer contained in the wet pad material which can be used in open spaces such as the traditional hall. bali, hotel lobby, restaurant with an open concept, and can be used as a cooler for chicken coops and to maintain the freshness of fresh agricultural fruit and vegetables. This research was conducted to analyze the wettability and surface roughness of Betung bamboo charcoal as a pad material in a direct evaporative system. cooling. Carbonization temperatures of 500oC, 600oC, 700oC, and 800oC are used. And the results obtained by increasing the carbonization temperature of the bamboo betung, the lower the wettability and surface roughness of the bamboo betung carbonization material. Keywords: Temperature, Carbonization, Betung Bamboo, Material, Wettability, Surface Roughness, Contact Angle